Aplicação aérea de grânulos de argila como veículo de herbicidas para o controle de plantas daninhas em área de reforma de eucalipto - Carbonari, Caio Antonio [UNESP] (2011)
An experiment was carried out in the eucalyptus area of Capão Bonito in the São Paulo state, Brazil, to evaluated the efficacy of the aerial application of the herbicides sulfentrazone and isoxaflutole using clay granules for weed control in Eucalyptus area. Aerial application of the herbicides sulfentrazone at 500 and 750 g a.i. ha-1 and isoxaflutole at 150 e 225 g a.i. ha-1 , was carried out using clay granules with 1,05 g cm-3 density, high absorption capacity (24 ml 100 g-1 ), high wear resistance, and particle size between 500 microns and 1 mm. Liquid spraying was also performed using the same herbicides at the same doses. A check plot without herbicide application was also used. Brachiaria decumbens, Ipomoea grandifolia, Merremia cissoides e Panicum maximum were sown in the experimental plot, and control evaluations being conducted at 75 and 110 days after application. A low level control was observed for both herbicides at lower doses. Sulfentrazone at 750 g a.i. ha-1 showed better control of B. decumbens and P. maximum for the aerial application of clay granules and similar results to both applications techniques on other weeds tested. The isoxaflutole at 215 g a.i. ha-1 showed superior weed control for liquid spraying at the beginning and similar and superior results for the aerial application in the final evaluation, indicating an extension of residual effect of herbicide.